PEMBERDAYAAN KOMUNITAS LOKAL MELALUI PENDEKATAN KREATIF MARKETING: STUDI KASUS DI SEKTOR INDUSTRI RUMAHAN - Sovania, Erina (Jurnal Abdi Masyarakat, 2024)
This community service activity focuses on empowering local SMEs in the home industry sector in North Jakarta through creative marketing strategies. The subjects of the program are home-based SMEs lacking knowledge and skills in digital marketing. The primary objective is to enhance their understanding and application of innovative marketing strategies to improve market reach and competitiveness. The method used is participatory training and workshops that provide hands-on experiences in storytelling, content marketing, influencer marketing, and the use of augmented reality (AR). The results show increased awareness and readiness among participants to adopt creative marketing strategies, reflecting a positive shift in their marketing approach. However, further research is needed to measure the actual impact of these strategies on sales and consumer engagement after implementation.